Tied and Bound: A Comparative View on Manuscript Binding - Bausi, Alessandro; Friedrich, Michael (Studies in Manuscript Cultures, 2023)
Every book form - from China to West Africa, from Europe to Mesopotamia - requires a way to secure cohesion of its constituent elements and keep them together. Whereas codex binding, as it still appears in modern printed books, is a familiar device, a comparative view on how things have been kept together in historic and current manuscript cultures provides an eye-opening survey of the variety of strategies applied to tie and bind manuscripts.